Control of COVID-19 in Rural Area: An Evidence-based Strategy - Mohammad Khammarnia; Seyed Mohammad Hashemi-Shahri; Alireza Ansari-Moghaddam; Seyed Mehdi Tabatabaei; Ali Naghizadeh; Mohammadhadi Abbasi; Seyed Mohammad Nasiruddin Tabatabaei; Fatemeh Setoodehzadeh; Mehdi Zangane Bayegi; Majid Sartipi (Shiraz University of Medical Sciences, 2022)
Background: COVID-19 has become a global problem. In this case study, the experiences gained from disease control in rural areas are reported. Methods: An observational study was done in 2020 in Sistan and Balochestan, the largest province with most rural areas in the southeast of Iran. Results: After identification of the first patient of Covid-19 in a rural area, three measures were taken including: 1. Diagnosis, screening and treatment of the disease (Incident command post was established and the village was completely quarantined, etc.; 2. Intersectoral coordination for epidemiological management (limiting traffic for people and any gathering); and 3. Identification of any Covid-19 positive cases. The results of these measures showed that after quarantining the village and performing the mentioned actions, the number of patients decreased, and the disease was controlled. Conclusion: Quarantine of the contaminated rural area and people's traffic routes is one of the most important measures in controlling Covid-19.